Semprotulation as a Post-Thesis Celebration Culture: Meanings, Symbols, and Its Pedagogical Implications for Language Learning in Higher Education - Saragih, Mandra; Saragih, M Afiv Toni Suhendra; Anam, Khairul (English Teaching and Linguistics Journal (ETLiJ), 2026)
Post-thesis celebrations in higher education are often viewed as informal or peripheral activities, yet they constitute rich communicative spaces where language, identity, and culture intersect. This study investigates Semprotulation, a student-initiated celebratory ritual performed after thesis defenses, to examine its meanings, symbols, and interactional dynamics as well as its pedagogical implications for language learning. Employing a qualitative-dominant mixed-method design, the research integrates ethnographic observation, multimodal discourse analysis, interviews, and questionnaires involving 48 students and 10 academic staff at an Indonesian university. Data were collected through video recordings, field notes, and participant reflections, and analyzed thematically and interactionally to identify recurring linguistic and symbolic patterns. The findings reveal that Semprotulation operates as a structured multimodal genre characterized by humorous teasing, congratulatory formulas, code-switching practices, embodied gestures, and symbolic artifacts such as water and flour that index renewal and solidarity. These practices facilitate emotional release, strengthen peer cohesion, and create authentic opportunities for spontaneous language use and digital literacy through social media documentation. From a sociolinguistic and pedagogical perspective, the ritual functions as an informal site of language socialization that complements formal instruction by fostering communicative confidence, identity negotiation, and collaborative learning. The study contributes to applied linguistics and language education by reframing campus cultural traditions as meaningful educational resources and recommends integrating students’ lived communicative practices into culturally responsive and multimodal language pedagogy.